Pneumonectomy for primary lung cancer: contemporary outcomes, risk factors and model validation. (6th December 2021) - Brunswicker, Annemarie; Taylor, Marcus; Grant, Stuart W; Abah, Udo; Smith, Matthew; Shackcloth, Michael; Granato, Felice; Shah, Rajesh; Rammohan, Kandadai; ,
Abstract: OBJECTIVES: Despite the increased rate of adverse outcomes compared to lobectomy, for selected patients with lung cancer, pneumonectomy is considered the optimal treatment option. The objective of this study was to identify risk factors for mortality in patients undergoing pneumonectomy for primary lung cancer. METHODS: Data from all patients undergoing pneumonectomy for primary lung cancer at 2 large thoracic surgical centres between 2012 and 2018 were analysed. Multivariable logistic and Cox regression analyses were used to identify risk factors associated with 90-day and 1-year mortality and reduced long-term survival, respectively. RESULTS: The study included 256 patients. The mean age was 65.2 (standard deviation 9.4) years. In-hospital, 90-day and 1-year mortality were 6.3% ( n = 16), 9.8% ( n = 25) and 28.1% ( n = 72), respectively. The median follow-up time was 31.5 months (interquartile range 9–58 months). Patients who underwent neoadjuvant therapy had a significantly increased risk of 90-day [odds ratio 6.451, 95% confidence interval (CI) 1.867–22.291, P = 0.003] and 1-year mortality (odds ratio 2.454, 95% CI 1.079–7.185, P = 0.044). Higher Performance Status score was associated with higher 1-year mortality (odds ratio 2.055, 95% CI 1.248–3.386, P = 0.005) and reduced overall survival (hazard ratio 1.449, 95% CI 1.086–1.934, P = 0.012). Advanced (stage III/IV) disease was associated with reduced overall survival (hazard ratio 1.433, 95% CI 1.019–2.016, P = 0.039). Validation of a pneumonectomy-specific risk model demonstrated inadequate model performance (area under the curve 0.54). CONCLUSIONS: Pneumonectomy remains associated with a high rate of perioperative mortality. Neoadjuvant chemoradiotherapy, Performance Status score and advanced disease emerged as the key variables associated with adverse outcomes after pneumonectomy in our cohort. Abstract : Lung cancer is the third most common cancer in the UK with over 47 000 new diagnoses each year [1].